The Relationship Between Interpersonal Communication Skills and Marital Satisfaction of Working Wife - Nining Maizura; Taufik Taufik (Jurnal Neo Konseling, 2021)
This research is motivated by the large number of married couples who experience divorce due to dissatisfaction in marriage. This study aims to describe: (1) interpersonal communication skills in working wives, (2) marriage satisfaction levels in working wives, and (3) finding a relationship between interpersonal communication skills and marriage satisfaction levels in working wives. The research subjects are 33 women who have been married for 6-10 years and work outside the home. The instrument used was a Likert scale model. Data analysis used is descriptive analysis with percentage techniques and for normality test, linearity test, and the relationship between the two variables used statistical analysis with Pearson Product Moment Correlation. The results of this study indicate that (1) the interpersonal communication skills of working wives are in the medium category with the average percentage of achievement 67%, (2) the level of marriage satisfaction of working wives is in the low category with the average percentage of achievement 59%, and (3) there is a significant positive relationship between interpersonal communication skills and marriage satisfaction in the wife who works for 0.891 with a significant level of 99%. Thus it can be interpreted that the higher the wife's interpersonal communication skills, the higher the level of marriage satisfaction and vice versa. Based on the research results, it is hoped that counselors in the city of Padang can provide assistance to women who are married and work, in the form of information services such as ways to avoid conflict.